Non-carbene Complex [RuCl2(PPh3)(2)(azocane)] as Active Catalyst Precursor for ROMP and ATRP - Silva, Rodolpho A. N. [UNESP]; Borim, Patricia [UNESP]; Fonseca, Larissa R.; Lima-Neto, Benedito S.; Silva Sa, Jose L.; Carvalho-, Valdemiro P. [UNESP] (Springer, 2017)
The novel, non-carbene complex -[RuCl2(PPh3) (2)(azocane)] (1) of trigonal bipyramid geometry was synthesized, characterized (CHN elementary analysis, FTIR, EPR, and 31P NMR), and applied as catalyst precursor for ring opening metathesis polymerization (ROMP) and atom transfer radical polymerization (ATRP). ROMP of norbornene (NBE) resulted in 70% yield at 50 degrees C in 60 min, with [NBE]/[1] = 5000, and 15% yield from ROMP of norbornadiene was obtained under the same conditions. ATRP of methyl methacrylate (MMA) resulted in ca. 20% conversion at 85 degrees C in 9 h, with [MMA]/[1] = 1000, and increased to ca. 50% in the presence of Al(OiPr) (3), with narrower PDI values. With [MMA]/[1] = 200, ca. 50% yield was obtained at 85 degrees C in 6 h either in the absence or presence of Al(OiPr) (3). ATRP of styrene resulted in 9 and 16% conversion at 110 degrees C in 7 h in the absence or presence of Al(OiPr) (3), respectively, with [St]/[1] = 1000. Results are discussed considering the five-coordinated molecular geometry of the starting complex and the arrangements required in ROMP and ATRP to initiate the reactions.
Keywords: Ruthenium; ROMP; ATRP; Norbornene; Norbornadiene; Methyl methacrylate; Styrene